Genetics, Epigenetics, and Gender Impact in Axial-Spondyloarthritis Susceptibility: An Update on Genetic Polymorphisms and Their Sex Related Associations - Chimenti, Maria Sole; Perricone, Carlo; D’Antonio, Arianna; Ferraioli, Mario; Conigliaro, Paola; Triggianese, Paola; Ciccacci, Cinzia; Borgiani, Paola; Perricone, Roberto (Frontiers in Genetics, 2021)
Spondyloarthritis (SpA) is a group of chronic inflammatory rheumatic disease that can be divided into predominantly axial or predominantly peripheral involvement, with or without associated psoriasis, inflammatory bowel disease or previous infection. Axial SpA (axSpA) encompasses ankylosing spondylitis (AS) with radiological sacroiliitis, and a type without radiographic sacroiliitis, called non-radiographic axial SpA” (nr-axSpA). Males and females show large differences in their susceptibility to SpA, such as distinctions in clinical patterns phenotypes and in therapeutical response, particularly to TNF inhibitors (TNFi). Several studies indicate that AS women have doubled risk to failure TNFi compared with males. This diversity in drugs’ efficacy among women and men may be caused by differences in sex hormones balance and in gene-specific expression likely triggered by X-chromosome instability and gene-specific epigenetic modifications. Evidence reported that polymorphisms in microRNAs on X- and other chromosomes, such as miR-146a, miR-155, miR-125a-5p, miR-151a-3p and miR-22-3p, miR-199a-5p could be involved in the different clinical presentation of SpA, as well as disease activity. In addition, association with non‐response to TNFi treatment and presence of IRAK3 and CHUCK genes in SpA patients was recently detected. Finally, polymorphisms in genes involved in IL-23/IL-17 pathway, such as in drug pharmacodynamics and pharmacokinetics may have a role in response to TNFi, IL17i and IL23i. A major understanding of genomic variability could help in the development of new therapeutic targets or in taking advantages of different mechanisms action of biological drugs. Moving from the multifactorial etiology of disease, the present review aims at evaluating genetic and epigenetic factors and their relationship with sex and bDMARDs response, helping to investigate the different expression among males and females of genes on X- and other chromosomes, as well as mi-RNA, to highlight relationships between sex and occurrence of specific phenotypes and symptoms of the disease. Moreover, the role of the epigenetic modification in relation to immune-regulatory mechanisms will be evaluated.